Halophilic bacteria of salt lakes and saline soils of the Peri-Caspian lowland (Republic of Daghestan) and their biotechnological potential - E. A. Khalilova; S. T. Kotenko; E. A. Islammagomedova; A. A. Abakarova; N. A. Chernyh; D. A. Aliverdiyeva (Вавиловский журнал генетики и селекции, 2021)
The article presents the results of studying the biodiversity and biotechnological potential of halophilic microorganisms from the thermal highly mineralized Berikey Lake, the salty Lake Tarumovskoye and saline soils of the Peri-Caspian Lowland (Republic of Daghestan). Denitrifying halophilic bacteria of the genus Halomonas and Virgibacillus were identified using microbiological methods and 16S rRNA gene analysis. A new species Halomonas sp. G2 (MW386470) with a similarity of the nucleotide sequences of the 16S rRNA genes is 95 %. Strain G2 is an extreme halophile capable of growing in the range of 5–25 % NaCl (optimum 25 %) and forming a carotenoid pigment. Mesophil, 30–37 °С (optimum 30 °С); neutrophil, pH 6–8 (optimum 7.2–7.4). Strain G2 chemolithotroph; reduces nitrate or nitrite as electron donors; catalase-, amylase-, protease- and β-galactosidase-positive; lipase-, oxidase- and urease-negative. Not able to hydrolyze inositol, indole; produces lysine, gelatin, ectoine; uses citrate and sodium malate as a source of carbon and energy; does not produce ornitin, H2S or acid from d-mannose, sucrose, glycerol, cellobiose, except for lactose and d-glucose. Susceptible to trimethoprim, ciprofloxacin, ofloxacin, kanamycin, vancomycin, rifampicin, cefuroxime, ampicillin, ceftazidime, fosfomycin, clarithromycin, cefepime, cefaclor. The G+C content in DNA is 67.3 %. A distinctive characteristic of the isolate was the production of industrially significant hydrolytic enzymes such as amylase, protease, β-galactosidase, and oxidoreductase (catalase) at a NaCl concentration of 25 % in the medium. Habitat: saline soils on the territory of the Tersko-Kumskaya lowland (Republic of Daghestan, Russia). The rest of the halophilic isolates of H. ventosae G1 (MW386469), H. elongata G3 (MW386471), V. salinarius B2 (MW386472), and V. salinarius B3 (MW386473) had a high degree of similarity (100 %) with the type strains of H. elongata DSM 2581Т and V. salarius DSM 18441Т; the content of G+C in DNA was 65.8, 66.5, 42.8 and 37.3 %, respectively. The strains had a high biotechnological potential at NaCl concentrations of 5 and 25 % in the medium. The data obtained expanded the understanding of the diversity and ecological significance of denitrifying bacteria in the functioning of arid ecosystems and make it possible to identify strains producing enzymes of industrial importance.